PRINCIPLES OF APPLICATION OF FINANCIAL ADMINISTRATIVE SANCTIONS IN THE LEGAL DOCTRINE OF UKRAINE AND THE WORLD - Ivan Shumeiko; Iryna Svitlyshyna; Olga Sokolenko (Baltic Journal of Economic Studies)
The focus of states on administrative sanctions has increased, with these sanctions being considered a higher priority than criminal sanctions in terms of combating offences. The application of such sanctions is relatively straightforward and expeditious. Furthermore, financial sanctions serve to replenish state budgets. Nevertheless, the administrative nature of such sanctions carries with it the risk of violating the fundamental rights of the individual who is the weaker party in these legal relations, given that the body that brings charges and the body that imposes the penalty usually coincide. The crux of the issue pertains to the necessity of adhering to the three principles of prohibition of double responsibility, presumption of innocence and proportionality. However, divergent schools of thought have divergent perceptions of the content of these principles and the extent of their application in the area of administrative sanctions. The purpose of this article is to ascertain the main principles of financial administrative sanctions as recognised by scholars in Ukraine and other countries worldwide. The article presents a comparative analysis of publications by Ukrainian and foreign scholars on three fundamental principles of legal liability in the context of financial administrative sanctions. The article also contains the author's point of view on the application and content of these principles. The authors define the term "administrative sanction" and describe the existence of this legal phenomenon in the legal system of Ukraine, as well as characterise related legal phenomena. The research is grounded in the study and comparison of doctrinal sources. The article is of a theoretical nature. The conclusions drawn can inform the processes of lawmaking and law enforcement, in addition to further scientific research.